Learning Media Design based on Traditional Game of Tumbu-Tumbu Belanga (T2B) on Salt Hydrolysis Topic - Tangio, Julhim S.; Patilima, Rusmiyati; La Kilo, Jafar; La Kilo, Akram (JCER (Journal of Chemistry Education Research), 2021)
This research aimed to test the validity of the feasibility of traditional game learning media on salt hydrolysis. This research was development research (R&D) with a qualitative descriptive approach. This research uses the ADDIE model development design, which consists of 5 (five) stages, namely (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. Data collection techniques in this study used a validation sheet for the assessment of the feasibility of tumbu-tumbu  learning media. The tumbu-tumbu  learning media validation wass assessed by 4 expert validators, namely 2 chemistry lecturers of State University of Gorontalo material experts, 1 media expert lecturer, and 1 high school chemistry teacher. The results of the validation of tumbu-tumbu  learning media development obtained an average percentage 0f 89.40%, which was categorized in very feasible criteria. Therefore, the tumbu-tumbu  learning media are highly usable in the learning process of salt hydrolysis.